An Analysis of the Role of Higher Education in Promoting Critical Thinking and Problem-Solving Skills among Pakistani Students - Dr. Shakeel Ahmed,; Dr. Shams Wazir,; Shazia Kazmi,; Shabana Kousar, (Dialogue Social Science Review (DSSR), 2025)
This study examined the role of higher education in promoting critical thinking and problem-solving skills among Pakistani students through a mixed-methods approach. A cross-sectional survey design was employed, targeting 450 undergraduate and graduate students from five major universities across Punjab, Sindh, and Khyber Pakhtunkhwa provinces. Data collection involved the California Critical Thinking Skills Test (CCTST), a self-developed questionnaire, and semi-structured interviews with faculty and students. Quantitative analysis revealed significant positive correlations between higher education experience and critical thinking abilities (r = 0.68, p < 0.001), with engineering students demonstrating the highest mean scores (M = 78.4, SD = 8.2). Qualitative findings highlighted the importance of interactive teaching methods, case-based learning, and research-oriented curricula in developing analytical skills. The study found that while Pakistani higher education institutions show promise in fostering critical thinking, gaps remain in systematic skill development across disciplines. Results indicate that students' problem-solving abilities improved significantly with academic progression, particularly in science and engineering fields. This research contributes to understanding educational practices in Pakistani universities and provides insights for curriculum enhancement to better prepare students for contemporary challenges. Keywords: Critical thinking, problem-solving skills, Higher education, Pakistani students, educational assessment, mixed-methods research, academic development.